2004
DOI: 10.1016/j.neuropsychologia.2003.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Head size and intelligence, learning, nutritional status and brain development

Abstract: This multifactorial study investigates the interrelationships between head circumference (HC) and intellectual quotient (IQ), learning, nutritional status and brain development in Chilean school-age children graduating from high school, of both sexes and with high and low IQ and socio-economic strata (SES). The sample consisted of 96 right-handed healthy students (mean age 18.0 +/- 0.9 years) born at term. HC was measured both in the children and their parents and was expressed as Z-score (Z-HC). In children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
123
2
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 63 publications
9
123
2
5
Order By: Relevance
“…The long-term neurobehavioral development of young children is largely dependent on the environment they are exposed to (12)(13)(14). Intrauterine exposure of the fetus to neuroteratogenic agents such as heroin, cocaine, and alcohol may have deleterious effects on long-term postnatal development (15,16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term neurobehavioral development of young children is largely dependent on the environment they are exposed to (12)(13)(14). Intrauterine exposure of the fetus to neuroteratogenic agents such as heroin, cocaine, and alcohol may have deleterious effects on long-term postnatal development (15,16).…”
mentioning
confidence: 99%
“…Intrauterine exposure of the fetus to neuroteratogenic agents such as heroin, cocaine, and alcohol may have deleterious effects on long-term postnatal development (15,16). Postnatal exposure of normal infants to a damaging environment, including nutritional deficiencies especially during the first year of life, may have long-lasting effects similar to those observed following intrauterine exposure (12,(17)(18)(19). Indeed, such long-term developmental consequences have been associated with deficiencies in several vitamins in childhood, including vitamin B 12 (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HC is also the most sensitive anthropometric indicator of prolonged malnutrition during infancy and can be associated with intellectual impairment (Ivanovic et al, 2000(Ivanovic et al, , 2002. Malnutrition alters brain development and intelligence in a multi-causal context, and poverty and deprivation exacerbate these negative effects, especially when these factors persist throughout a lifetime (Ivanovic et al, 2004). Under these conditions, a stable environment that provides adequate stimulation is very difficult to achieve, and for this reason the brain damage caused by malnutrition at an early age frequently is not reversible (Brown and Pollitt, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the effect of malnutrition on cognitive development has remained difficult, due to covarying risk factors and the inability to perform randomized controlled studies (Grantham-McGregor, 1995). A number of studies have shown a small long-term negative effect of malnutrition on IQ after adjusting for socioeconomic factors and education (Freeman et al, 1980;Galler et al, 1983Galler et al, , 1990Rose, 1994;Mendez & Adair, 1999;Ivanovic et al, 2000Ivanovic et al, , 2004Berkman et al, 2002;Jianghong et al, 2003). However, these studies have not controlled for parental IQ.…”
Section: Introductionmentioning
confidence: 99%